HITUNG KOLONI Candida Albicans DI TINJA ANAK GANGGUAN AUTISM SPECTRUM - R Herawati; I Parwati; I Sjahid; C. Rita (Indonesian Association of Clinical Pathologist and Medical laboratory, 2006)
Candida albicans is part of the normal flora of the digestive tract, however in immunocompromised host can cause opportunisticinfection. According to Shaw’s case series study in North Carolina USA, colonization of C. albicans is increased in autism spectrumdisorders (ASD) patients. C. albicans is a dimorphism fungus, the yeast phase is grown at 37 °C and the mould phase is grown at roomtemperature. The aim of this study was to compare C. albicans colony count in stools of ASD patients and normal children, and to findcorrelation between C. albicans colony count and state of ASD. A cross sectional study was conducted from December 2004 to March 2005on 50 ASD patients and 50 normal children as controls. Diagnosis of ASD was based on the Diagnostic and Statistical Manual of MentalDisorders (DSM) IV criteria. The range of age in both groups was 2 to 6 years old. Stool specimens were collected in Sachs transportmedia. All specimens were examined in the Division of Infectious and Tropical Medicine, Department of Clinical Pathology RSHS/FKUPBandung. The specimens were examined microscopically and cultured on Sabouraud dextrose agar incubated at room temperature and37 °C. The colonies were interpreted in colony forming unit (CFU). The C. albicans was identified by colony microscopic examinationand germ tube test. The differences of C. albicans colony count between ASD and normal subject were analyzed by t-test. Correlationbetween colony count C. albicans and ASD state was analyzed using point biserial correlation. Of 50 subjects, 14 (28%) were diagnosedas pervasive developmental disorder not otherwise specified (PDD-NOS) and 36 (72%) were diagnosed as autistic disorders. There wereno significant statistical differences between ASD and normal subjects in age, sex, and nutritional status (p > 0.05). A significantcorrelation between direct microscopy and the result of Candida colony count was found (p = 0.0000). We did not find a significantdifference between the two temperature of incubations (p = 0.390). Mean of C. albicans colony count in normal subjects was 4 CFU.In contrast, the mean of C. albicans colony count in ASD subjects was 39 CFU. The mean C. albicans colony count in ASD subjects wassignificantly higher than normal subject (p = 0.012). There was a significant correlation between C. albicans colony count and the stateof ASD (Rpb0.253372; p = 0.0106) : C. albicans colony count from stool of ASD subjects was significantly higher than normal subjects.We also found a significant correlation between C. albicans colony count and the state of ASD